Analisis Dampak Pembangunan Smelter terhadap Sosial Ekonomi Masyarakat Tani di Desa Morosi Kecamatan Morosi Kabupaten Konawe - Rahman, La Ode Abdul; Pandangaran, Ayub Mangala; Surni, Surni (Jurnal Ilmiah Membangun Desa dan Pertanian, 2019)
The purpose of this study was to determine the socio-economic impacts caused by the construction of smelters on farmers. This research was conducted in January 2018 with a total sample of 34 people determined by simple random sampling. Analysis of the data used is the analysis of different test analysis by comparing scores before and scores after the smelter. Based on the description of results of the study, the conclusion of this study is that the impact caused by the construction of a smelter on the socio-economic community, namely the contructions of smelters opening opportunities for employment of respondents who work as farm laborers to factory workers and other jobs such as motorcycle taxi and merchants and the increased income was followed by an increase in prices of basic commodities so that the constructions of the smelter did not have a major impact on the farming community in the village of Morosi, the Morosi District, Konawe District.